Loving-kindness meditation (LKM) modulates brain-heart connection: An EEG case study - Wong, GoonFui; Sun, Rui; Adler, Jordana; Yeung, Kwok Wah; Yu, Song; Gao, Junling (Frontiers in Human Neuroscience, 2022)
Loving-Kindness Meditation (LKM) is an efficient mental practice with long history that has recently attracted interest in the neuroscience, medical and education fields. However, the neural characters and underlying mechanism have not been fully illustrated, which hinders its practical usefulness. This study aimed to investigate LKM from aspects of interactions brain, heart and psychological measurements. A Buddhist monk practitioner was recruited to complete one 10-minute LKM and two 10-minute resting tasks (pre- and post-resting). Two sets of single-channel wearable EEG devices were used to collect EEG (placed at Fz and Pz) and heart rate simultaneously. A comprehensive performance evaluation was conducted in each session by filling a self-designed report. Spectrum analysis showed a significant increase of theta power (Fz: t = -3.356; p = 0.002; Pz: t = -5.199; p < 0.001) and decrease of heart rate between pre- and post-resting tasks (t = 4.092, p < 0.001). The analysis showed a negative correlation between theta power and heart rate (Fz: r = -0.681, p < 0.001; Pz: r = -0.384, p = 0.008), and positive correlation between theta power and the self-designed report score (Fz: r= 0.601, p < 0.001). These findings suggest that LKM is accompanied by significant neurophysiological changes, mainly increasing the slow-wave such as theta wave and decreasing heart rate. The heart-brain connection increases after LKM meditation. More importantly, subjective psychological assessment is correlated with objective neurophysiological measurement in a long-term meditator. The use of the wearable device for LKM implicates its potential in real-life.